Dredging and reclamation of Sarawak river estuary with the application of swan - Ahmadi, Hashim. (Universiti Malaysia Sarawak, UNIMAS, 2009)
Sarawak River estuary faced critical erosion by ocean surface wave nowadays. Not only exposed to high energy wave condition from South China Sea, but also due to navigation channel. Hence, wave models are needed to control and then overcome this problem. Using the SWAN (Simulating WAve Nearshore) wave modeling, the physical wave parameters were investigated to determine the wave condition nearshore. This investigation is carried out to predict the wave generation, refraction and energy dissipation at Sarawak River estuary with dredging and reclamation bathymetry, and using the previous data of local wind and wave. The bathymetry map is digitized in SURFER where dredging and reclamation is visualized to view the bottom data. The wave model was developed for Annual, Northeast Monsoon and Southwest Monsoon wave condition. Design waves are analyzed using statistical method of short term and long term analysis. Short term analysis is presented by significant wave height of average height of the one third highest waves (H1/3), while, long term analysis comprises of extreme value from Gumbel and Weibull statistical distribution analysis. The outputs from this model are significant wave height (H s ), mean wave period (Tm01) and wave direction (Dir) for each chose location. The H s , Tm01 and Dir are different for each location.